2022
DOI: 10.32604/jrm.2021.015854
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mutual Improvement of Completed Weathered Phyllite and Red Clay Based on Neutralization Effects of Swelling and Shrinkage Deformation

Abstract: Completely weathered phyllite (CWP) soil is a kind of special soil with high swell potential, while red clay is a special soil with high shrinkage. This means that these two kinds of special soils are usually not suitable for direct use as subgrade fill. To reduce the swell index of the CWP soil and the shrinkage of red clay at the same time, it was proposed to blend the CWP soil with red clay to improve their basic characteristics. A series of swell index tests and dry-wet cycle tests of the blended soils hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The disintegration of soil is closely related to the mineral composition, and the mineral content of the two type soils is determined by a semi-quantitative XRD test, as shown in Table 3. The phyllite soil contains montmorillonite, illite, and chlorite, which are three kinds of hydrophilic clay minerals accounting for 40.6% of the total mass of phyllite soil (montmorillonite is a typical expansive mineral) and which are prone to swell and deformation after being soaked in water [28]. According to the laboratory free expansion test, the free expansion ratio of phyllite soil reaches 19.4%.…”
Section: Influence Of Mineral Composition and Particle Size On Disint...mentioning
confidence: 99%
See 1 more Smart Citation
“…The disintegration of soil is closely related to the mineral composition, and the mineral content of the two type soils is determined by a semi-quantitative XRD test, as shown in Table 3. The phyllite soil contains montmorillonite, illite, and chlorite, which are three kinds of hydrophilic clay minerals accounting for 40.6% of the total mass of phyllite soil (montmorillonite is a typical expansive mineral) and which are prone to swell and deformation after being soaked in water [28]. According to the laboratory free expansion test, the free expansion ratio of phyllite soil reaches 19.4%.…”
Section: Influence Of Mineral Composition and Particle Size On Disint...mentioning
confidence: 99%
“…In this paper, a novel method is proposed by adding cement and red clay simultaneously to phyllite soil to improve its permeability and disintegration characteristics. Previous studies have shown that red clay can significantly improve the direct subgrade-bearing capacity of phyllite soil [27], and phyllite soil can significantly reduce the cracks caused by the wetting-drying cycle of red clay [28]. The seven-day saturated unconfined compressive strength of a cement-treated phyllite blended with red clay can be greater than 350 kPa [29].…”
Section: Introductionmentioning
confidence: 99%
“…There are no specific reference opinions on the relaxation requirements for compaction and moisture content, and the engineering characteristics of red clay fillers vary in different regions [ 12 , 13 ]. Therefore, it is urgent to start from the basic needs of filling red clay embankments, exploring the relationship between the basic physical and mechanical indicators of Guangxi red clay and the changes in compaction and moisture content and providing guidance for engineering construction [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional methods of improving weathered phyllite with cement or lime mainly consider the longterm strength and long-term stability of subgrade fill, but a significant amount of cement or lime is required to achieve this [9,10]; Using red clay to improve CWP soil mainly considered the immediate strength [27], and the method can not only reduce the expansibility of CWP, but also reduce the fissures in red clay [29]. However, this type of improvement method is only suitable for ordinary railway subgrade applications but cannot satisfy the subgrade requirements for the high-speed railway.…”
Section: Introductionmentioning
confidence: 99%